Mysteries in embryonic development: How can errors arise so frequently at the beginning of mammalian life? - Schneider, Isabell; Ellenberg, Jan (PLoS biology, 2019)
Chromosome segregation errors occur frequently during female meiosis but also in the first mitoses of mammalian preimplantation development. Such errors can lead to aneuploidy, spontaneous abortions, and birth defects. Some of the mechanisms underlying these errors in meiosis have been deciphered but which mechanisms could cause chromosome missegregation in the first embryonic cleavage divisions is mostly a “mystery”. In this article, we describe the starting conditions and challenges of these preimplantation divisions, which might impair faithful chromosome segregation. We also highlight the pending research to provide detailed insight into the mechanisms and regulation of preimplantation mitoses.